Making sense of experiences in suicide helpline calls: Offering empathy without endorsing suicidal ideation. Issue 9 (11th October 2021) - Iversen, Clara
Abstract: The question of how people make sense of experiences in relation to health is central to medical sociology and lies at the heart of suicide helpline practice. This article draws on a corpus of 900 audio‐recorded suicide helpline calls to examine how call‐takers respond to the challenge of reframing callers' suicidal ideation while still treating their experiences as legitimate. Conversation analysis of a subselection of calls revealed two call‐taker practices, involving the framing of the caller's suicidal ideation as (1) being ambivalent or (2) having legitimate feelings in a difficult situation. While callers resisted the former, 'feeling formulations' laid the interactional foundations for exploring alternatives to suicide. This may be because call‐takers' empathy increased their rights to subtly negotiate callers' experiences. By focusing on recipients' contributions in these critical interactional moments, the article widens the sociological approach to examining sense‐making of health experiences as a thoroughly social process.